Impact of digital transformation factors on business performance of 5-star hotels in Ho Chi Minh City, Vietnam - Chau, Chon (Technium Social Sciences Journal, 2026)
This study analyzes the impact of digital transformation factors on the business performance of 5-star hotels in Ho Chi Minh City. Based on the Resource-Based View (RBV) theory and Dynamic Capabilities Theory, the research model proposes five constituent factors of digital transformation including: technological infrastructure, process digitalization, data analytics, digital service innovation, and innovation capability. Data were collected through surveys of hotel managers and processed using multiple linear regression method. The results show that all factors have positive and statistically significant impacts on business performance of 5-star hotels in Ho Chi Minh City, among which technological infrastructure and data analytics have the strongest influence. The study provides empirical evidence on the strategic role of digital transformation in enhancing competitiveness and sustainable development of high-end hotel enterprises in general and in Ho Chi Minh City, Vietnam in particular.